2003
DOI: 10.2337/diabetes.52.6.1502
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Advanced Glycation End Products in Diminished Bone Healing in Type 1 Diabetes

Abstract: The effect of type 1 diabetes on bone healing and bone formation in standardized craniotomy defects created in BALB/cByJ mice was determined. The hypothesis that advanced glycation end products (AGEs) contribute to diminished bone healing in diabetes was evaluated by assessing for the presence of the receptor for advanced glycation end products (RAGE) by immunohistochemistry in healing craniotomy defects in diabetic animals. The effect of local application of a known RAGE protein ligand, N ⑀ -(carboxymethyl)ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
183
1
23

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 219 publications
(216 citation statements)
references
References 54 publications
(46 reference statements)
9
183
1
23
Order By: Relevance
“…CML-collagen was prepared by chemical modification of acid soluble bovine skin collagen (Sigma), as previously described (23,38). Briefly, 50 μg of collagen was dissolved 1 mM HCl followed by incubation in sodium cyanoborohydride and glyoxylic acid in PBS.…”
Section: Cml-collagenmentioning
confidence: 99%
See 1 more Smart Citation
“…CML-collagen was prepared by chemical modification of acid soluble bovine skin collagen (Sigma), as previously described (23,38). Briefly, 50 μg of collagen was dissolved 1 mM HCl followed by incubation in sodium cyanoborohydride and glyoxylic acid in PBS.…”
Section: Cml-collagenmentioning
confidence: 99%
“…AGEs may exert a negative effect on bone by interfering with osteoblast differentiation and the production of matrix proteins such as collagen and osteocalcin (13,33,38,54). It has recently been reported that AGEs stimulate apoptosis of human mesenchymal stem cells which could limit the formation of adipose tissue, cartilage and bone (25).…”
Section: Introductionmentioning
confidence: 99%
“…CML-collagen-CML-collagen was prepared by chemical modification of acid-soluble bovine skin collagen (Sigma), as described previously (21,42). Briefly, 50 mg of collagen was dissolved in 25 ml of 1 mM HCl freshly made in sterile water and incubated at 37°C with occasional mixing.…”
Section: Methodsmentioning
confidence: 99%
“…These include diabetes-associated cataract formation, nephropathy, retinopathy, neuropathy, and periodontal disease (15)(16)(17)(18)(19)(20). AGEs also impair osseous wound healing (21).…”
mentioning
confidence: 99%
“…1) (Santana et al 2003). Defects were created in anesthetized mice with shaved heads and a midline incision with a carbide cylinder square bur (Meisinger cat#BA-2021-010) under normal saline irrigation.…”
Section: Methodsmentioning
confidence: 99%